2013
DOI: 10.1126/science.1241930
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral RNA Interference in Mammalian Cells

Abstract: In antiviral RNA interference (RNAi), the DICER enzyme processes virus-derived double-stranded RNA (dsRNA) into small interfering RNAs (siRNAs) that guide ARGONAUTE proteins to silence complementary viral RNA. As a counterdefense, viruses deploy viral suppressors of RNAi (VSRs). Well-established in plants and invertebrates, the existence of antiviral RNAi remains unknown in mammals. Here, we show that undifferentiated mouse cells infected with encephalomyocarditis virus (EMCV) or Nodamura virus (NoV) accumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
428
1
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 354 publications
(449 citation statements)
references
References 46 publications
16
428
1
4
Order By: Relevance
“…As mentioned previously, failure to document this process in the context of viral infection is complicated by the possibility that the virus encodes VSRs (Haasnoot et al , 2007; Wu et al , 2010). Therefore, we designed a virus‐free assay to measure long dsRNA‐mediated gene silencing at the single‐cell level and tested it initially in mouse embryonic stem cells (mESCs), in which the presence of dsRNAi and antiviral RNAi has been reported (Billy et al , 2001; Yang et al , 2001; Paddison et al , 2002; Maillard et al , 2013). mESCs stably expressing a GFP reporter gene were transfected with in vitro synthesised Cy5‐labelled long dsRNA corresponding to the first 200 nt of either the GFP (dsRNA‐GFP) or, as a control, the Renilla luciferase (dsRNA‐ RL ) coding sequences; GFP expression in live single Cy5‐positive (transfected) cells was then measured by flow cytometry (Fig 1A and B).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As mentioned previously, failure to document this process in the context of viral infection is complicated by the possibility that the virus encodes VSRs (Haasnoot et al , 2007; Wu et al , 2010). Therefore, we designed a virus‐free assay to measure long dsRNA‐mediated gene silencing at the single‐cell level and tested it initially in mouse embryonic stem cells (mESCs), in which the presence of dsRNAi and antiviral RNAi has been reported (Billy et al , 2001; Yang et al , 2001; Paddison et al , 2002; Maillard et al , 2013). mESCs stably expressing a GFP reporter gene were transfected with in vitro synthesised Cy5‐labelled long dsRNA corresponding to the first 200 nt of either the GFP (dsRNA‐GFP) or, as a control, the Renilla luciferase (dsRNA‐ RL ) coding sequences; GFP expression in live single Cy5‐positive (transfected) cells was then measured by flow cytometry (Fig 1A and B).…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, plant and insect viruses have evolved virulence factors called viral suppressors of RNA silencing (VSRs) that block various steps of the antiviral RNAi mechanism (Haasnoot et al , 2007; Wu et al , 2010). Experimental appreciation of the effects of RNAi on virus accumulation therefore requires the use of VSR‐deficient viruses (Deleris et al , 2006; Wang et al , 2006a; Diaz‐Pendon et al , 2007; Maillard et al , 2013). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Dicer's catalytic function appears mainly confined to precursor microRNA (pre‐miRNA) processing, and its antiviral capacity in mammals remains much debated (Parameswaran et al , 2010; Cullen et al , 2013; Li et al , 2013, 2016; Maillard et al , 2013; Backes et al , 2014; Ding & Voinnet, 2014; Kennedy et al , 2015; Jeffrey et al , 2017; tenOever, 2017). Some studies have reported that RNAi can impact antiviral immunity in mammals during influenza A virus, hepatitis C virus, Nodamura virus and, more recently, human enterovirus 71 infection (Wang et al , 2006; Matskevich & Moelling, 2007; Li et al , 2013, 2016; Maillard et al , 2013; Qiu et al , 2017). In contrast, others have found low abundance of viRNAs in mammalian somatic cells infected with various viruses, and only a modest effect of Dicer deficiency on viral replication, suggesting that RNAi is not an active mechanism of antiviral defence in most mammalian cell types (Parameswaran et al , 2010; Girardi et al , 2013; Backes et al , 2014; Bogerd et al , 2014; Schuster et al , 2017).…”
Section: Introductionmentioning
confidence: 99%